2017
DOI: 10.37922/pijmit.2017.v06i01.001
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of Indian Post in Financial Inclusion and Socio-Economic Empowerment

Abstract: Consumers develop their perception about the quality of services provided by restaurants based on the facilities the restaurant has and the behavior of their employees with consumers. The study was aimed at evaluating the causal effect of physical facilities and the behavior of employees of a restaurant. The data for the study was collected from the consumers immediately after they had enjoyed the services of restaurants located at Gwalior through survey using separate structured questionnaire on each variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The economic empowerment of women improves productivity, broadens the economy, by promoting income equality and it involves in other positive development outcomes. [1] It should be noted, nevertheless, that progress does not always equate to a decline in gender-based inequality. For example, raising female employment rates in OECD nations to Sweden's level may boost GDP by USD 6 trillion [11].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The economic empowerment of women improves productivity, broadens the economy, by promoting income equality and it involves in other positive development outcomes. [1] It should be noted, nevertheless, that progress does not always equate to a decline in gender-based inequality. For example, raising female employment rates in OECD nations to Sweden's level may boost GDP by USD 6 trillion [11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Acquiring the inner and external resources required making self-decisions, such as choosing one's living situation and diet, and exercising control over one's surroundings and way of life, can be a part of social empowerment on an individual level. [1] At the collective level, social empowerment entails the creation of communities, organizations, and groups that may cooperate to address shared issues and bring about change. Building social networks, acquiring leadership abilities, and encouraging social cohesiveness and solidarity are some examples of how to do this.…”
Section: Literature Reviewmentioning
confidence: 99%
“…All these above-cited reasons make the segment a challenging one for the government to include them in the process of financial inclusion. The silver lining is that whatever efforts the government has initiated show the result, and street vendors are slowly making themselves interested in the digital economy in order to be a part of it (Andotra & Manhas, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A large numbers of synthetic 1H-indazole-containing drugs and clinical candidates have been identified over the past few years Chang and co-workers reported a large number of compounds with 1H-indazole core structure. In addition to the synthesis and evaluation of the anticancer activity of these compounds, they have revealed some SAR and pharmacophore modeling data [4,5,[9][10][11][12][13]. Research on 1-and 3-aroylindoles9 showed that 3-substituted 1H-indazole derivatives exhibited significant activity compared with 1-aroyl1H-indazoles and the electronic effects on the 1H-indazole ring were important for activity potency [11].…”
Section: Introductionmentioning
confidence: 99%
“…Different classes of oxadiazole compounds possess an extensive spectrum of pharmacological activities. Differently substituted oxadiazole moiety has also been found to have other important activities such as antibacterial [12], antimalarial [13], antiinflammatory [14], antifungal [15], anticonvulsant [16], analgesic [17], antimicrobial [18], antimycobacterial [19], anticonvulsant [20], antitumor [21], antimalarial [22], herbicidal [23], vasodialatory [24], cytotoxic [25], hypolipidemic [26] ulcerogenic [27] (Figure 1) and (Table 1).…”
Section: Introductionmentioning
confidence: 99%